تقويم مدى ملاءمة معايير المحاسبة الدولية في تطوير المحاسبة عن المسؤولية الاجتماعية - لقمان محمد أيوب الدباغ (PROSPECTIVE RESEARCHES, 2023)
The literature of accounting is full of information about social responsibility accounting to enrich it with intellectual contributions and to set out a theoretical and practical framework for the economic units. This intellectual trend in accounting has not got enough attention from accounting societies and international organizations among them is international accounting standards committee. This committee has to issue standards that help assessing and declaring different economic activities for a variety of organizations regardless of the social dimension of the economic until and its interaction with the environment. The committee has played an active role in developing this trend intellectual and spread it through accounting standards which control the accounting performance in this respect. The international accounting standards are considered, accountingly, unappropriate completely to develop accounting about social responsibility.